Redes de influência e empresariamento - o Movimento Todos Pela Educação enquanto porta-voz da educação brasileira - Almeida, Leia Raquel de (Universidade do Vale do Rio dos Sinos, 2024)
This thesis discusses the phenomenon of the entrepreneurialization of education. Its main objective was to examine the Todos pela Educação Movement and its status as a spokesperson for Brazilian education by analyzing the networks of influence that constitute it. The specific objectives included: contextualizing and understanding the networks of political influence in the entrepreneurialism of education; mapping the relationships and internal movements of the networks that make up the Todos Pela Educação Movement; and analyzing the Movement's place of speech, seeking to understand its constitution as a spokesperson for Brazilian education supported by the constitution of its network of influence. The methodological procedures used in the study were document analysis and network ethnography, based on the Actor-Network Theory and the use of Gephi software to visualize the network. The immersion in the Activity Reports from 2006 to 2020 as an empirical corpus made it possible to highlight, as categories, the constitution of networks, the construction of political plots and the network resonance that manifests itself in the technologies of performativity. In the analytical framework, authors such as Ulrich Beck, Richard Sennet, Peter Miller, Nikolas Rose, Viviane Klaus, Osvaldo LópezRuiz, Pierre Dardot, Christian Laval, Manuel Castells and Stephen Ball provided important insights for the research, endorsing the debate on the network society and on technologies in the transformation of the world, especially in the neoliberal rationality that favors the emergence of the entrepreneurialization of education. The thesis argues that networks of political influence function as a technology of performativity in a rationality that prioritizes competition and commodification. The Todos pela Educação Movement, as an example of this network of influence, acts as a spokesperson for Brazilian education, and its discourse is legitimized by the evidence presented about the educational context. The research contributes to the discussion on the entrepreneurialization of education, recognizing the new forms of network governance and how it impacts on educational policies.
Keywords: Todos Pela Educação; redes de influência; Políticas educacionais; Empresariamento; Etnografia de redes; All for Education; Influence Networks; Educational policies; Entrepreneurship; ACCNPQ::Ciências Humanas::Educação